Pengembangan kerukunan masyarakat multikultural melalui pendekatan agama - Desky, Harjoni; Rijal, Syamsul (Penerbit Universiti Kebangsaan Malaysia, 2021)
Studies on religious tolerance are very important to do, especially in the context of the pluralistic Indonesian nation. In the framework of multiculturalism, religion must transcend the boundaries of language, ethnicity and also particular cultures. Religion is no longer itself separate from worldly projects and other dimensions. Religion that has entered a multicultural society will experience an acculturation process so that religion can have many versions, especially in the aspect of implementation. Starting from the perspective of understanding to the importance of religion in accordance with the culture of each region or place. It is from this multicultural society that differences in expression are born in carrying out religious orders. The role becomes very important when religion has been embraced by human social groups, which are associated with meeting the complex needs of human life in society. In a sociological perspective, religion is seen as a belief system that is manifested in certain social behaviors. Religion deals with human experience, both as individuals and groups. Therefore, the behavior played by individuals or groups will be related to the belief system of their religious teachings. Individual and social behavior is driven by internal strength, which is based on internalized religious values and has become one of the important pillars in shaping a harmonious, just and prosperous society.